THE ELIMINATION OF SECURITIES HELD IN THE ENTITIES WITHIN THE GROUP. ACCOUNTING APPROACH IN THE CONTEXT OF THE CONSOLIDATION OF ACCOUNTS (I) - Deju, Mihai (Studies and Scientific Researches. Economics Edition, 2021)
The existence of groups of companies is a relatively new issue for professional accountants, the academic environment, as well as for regulatory bodies in the field of accounting in Romania. In this context, the theoretical and practical aspects of the preparation of the consolidated annual financial statements generate extensive debates among accounting specialists, in order to find practical solutions to support the understanding and correct application of accounting regulations in the field of the consolidation of accounts. In two articles, we will present the accounting treatment of the disposal of securities held, within subsidiaries, associates, as well as in jointly controlled companies, by companies that prepare consolidated annual financial statements. The issue of disposal of securities held with entities whose individual financial statements are subject to consolidation will be presented in the form of case studies, structured as follows: Elimination of securities held with affiliated entities (object of this article); Elimination of securities held in associates and jointly controlled entities (joint ventures) - object of the next article.